Thermal and humid environment of rammed-earth dwellings in Northwest Sichuan. Issue 3 (March 2022) - Liang, Jiahua; Tan, Jiaye; Jiang, Bin
As a traditional building material, rammed earth has gained popularity for its environmental friendliness and reusability. In this study, the hygrothermal performance of the wall material of traditional rammed-earth dwellings was experimentally measured, and the indoor and outdoor temperature and humidity variations of rammed-earth dwellings were experimentally measured for five days. Considering temperature and relative humidity as the driving potential for heat and humidity transfer and air penetration, an unsteady model of heat and humidity transfer of the rammed-earth wall and indoor and outdoor air was established. The accuracy of the model was verified using the measured data. The model was used to determine the rationality of the wall thickness in local rammed-earth dwellings. Based on data from typical local meteorological years, the indoor temperature and humidity changes in rammed-earth dwellings were numerically predicted. The average indoor temperature and humidity in summer were 26.56°C and 69.74%, and the variances were 3.26 and 43.17, respectively. The average indoor temperature and humidity in winter were 7.25°C and 83.62%, and the variances were 1.14 and 14.83, respectively. The research results demonstrate that a rammed-earth wall significantly reduces the influence of outdoor temperature fluctuation on the indoor thermal environment, with good humidity regulating performance.